Brain sub/region-specific effects of olanzapine on c-Fos expression of chronically socially isolated rats - Stanisavljević, Andrijana; Perić, Ivana; Gass, Peter; Inta, Dragos; Lang, Undine E.; Borgwardt, Stefan; Filipović, Dragana (Neuroscience, 2018)
Olanzapine (Olz) is an atypical antipsychotic used to treat depression, anxiety and schizophrenia, which can be caused by chronic psychosocial stress. c-Fos protein expression has been used as an indirect marker of neuronal activity in response to various forms of stress or pharmacological treatments. We examined the effects of a 3-week treatment of Olz (7.5mg/kg/day) on c-Fos protein expression in stress-relevant brain sub/regions, its relationship with isolation-induced behavioral changes, and potential sites of Olz action on control and male rats exposed to 6weeks of chronic social isolation (CSIS), an animal model of depression. Olz treatment reversed depression- and anxiety-like behaviors induced by CSIS and suppressed a CSIS-induced increase in the number of c-Fos-positive cells in subregions of the dorsal hippocampus, ventral (v) DG, retrosplenial cortex, and medial prefrontal cortex. In contrast, no change in c-Fos expression was seen in the CA3v, amygdala and thalamic, hypothalamic or striatal subregions in Olz-treated CSIS rats, suggesting different brain sub/regions’ susceptibility to Olz. An increased number of c-Fos-positive cells in the CA1v, amygdala and thalamic, hypothalamic and striatal subregions in controls as well as in the CA1v and subregion of the hypothalamus and nucleus accumbens in Olz-treated CSIS rats was found. Results suggest the activation of brain sub/regions following CSIS that may be involved in depressive and anxiety-like behaviors. Olz treatment showed region-specific effects on neuronal activation. Our data contribute to a better understanding of the mechanisms underlying the CSIS response and potential brain targets of Olz in socially isolated rats.